PENGARUH KECERDASAN EMOSIONAL, KOMITMEN ORGANISASIONAL DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA MAHOTTAMA KABUPATEN KLUNGKUNG - I Nengah Sancaya; Gede Gama; Putu Agus Eka Rismawan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
This study aims to determine the effect of Emotional Intelligence, Organizational Commitment and Organizational Citizenship Behavior (OCB) on Employee Performance. The research sample consisted of 58 people who were taken by the Slovin method from 140 employees. The collected data were analyzed using multiple linear regression. From the analysis obtained, 1) Emotional Intelligence has a positive and significant effect on employee performance at PDAM Tirta Mahottama Klungkung Regency. This is evident from the significant effect and the regression coefficient shows a positive direction. 2) Organizational commitment has a positive and significant effect on the employee performance of PDAM Tirta Mahottama Klungkung Regency. This is evident from the significant effect and and the regression coefficient shows a positive direction. 3) Organizational chitizenship behavior has a positive and significant effect on the employee performance of PDAM Tirta Mahottama Klungkung Regency. This is evident from the significant effect and the regression coefficient shows a positive direction.